Comprehensive HIV Prevention for Transgender Persons - Neumann, Mary Spink (Am J Public Health, 2017)
Transgender persons are at high risk for HIV infection, but prevention efforts specifically targeting these people have been minimal. Part of the challenge of HIV prevention for transgender populations is that numerous individual, interpersonal, social, and structural factors contribute to their risk. By combining HIV prevention services with complementary medical, legal, and psychosocial services, transgender persons’ HIV risk behaviors, risk determinants, and overall health can be affected simultaneously. For maximum health impact, comprehensive HIV prevention for transgender persons warrants efforts targeted to various impact levels—socioeconomic factors, decision-making contexts, long-lasting protections, clinical interventions, and counseling and education. We present current HIV prevention efforts that reach transgender persons and present others for future consideration.